2010
DOI: 10.1039/c0cc00684j
|View full text |Cite
|
Sign up to set email alerts
|

White phosphorus and metal nanoparticles: a versatile route to metal phosphide nanoparticles

Abstract: P(4) reaction with metal NPs (In, Pb, Zn) provides an easy access to the corresponding metal phosphide NPs in a soft and stoichiometric reaction. Size-influence on the reactivity is investigated in the case of indium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 39 publications
2
62
0
Order By: Relevance
“…Solid Ni 2 P particles have also been made by the reaction of either nickel particles or Ni(C 8 H 12 ) 2 with P 4 . 102,103 In this chapter, we have shown how the chemistry described previously can be applied to the synthesis of more unusual materials. This demonstrates how general the chemistry is and how most materials should be accessible using the synthetic pathways described.…”
Section: Other Pnictide-based Materialsmentioning
confidence: 98%
“…Solid Ni 2 P particles have also been made by the reaction of either nickel particles or Ni(C 8 H 12 ) 2 with P 4 . 102,103 In this chapter, we have shown how the chemistry described previously can be applied to the synthesis of more unusual materials. This demonstrates how general the chemistry is and how most materials should be accessible using the synthetic pathways described.…”
Section: Other Pnictide-based Materialsmentioning
confidence: 98%
“…This coalescence results in an increased saturation magnetization compared to the thin films of MnSb (thickness 5 nm), followed by increased polar magnetic dichroism, which is an indication of the active magneto-optical properties of these MnSb dots. While the synthesis of colloidal transition metal phosphide particles has become quite routine, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and precedent exists for colloidal transition metal arsenide nanoparticles; [23][24][25][26][27][28][29] examples of antimonide colloids that exhibit narrow size polydispersity are quite few and typically limited to main group semiconductors. These nanostructures comprise nearly 50% of the MnSb film.…”
mentioning
confidence: 99%
“…[57] However, all these approaches were unable to provide a reliable synthesis route for monodispersed and highly luminescent InP-based QDs. In this work, I developed a synthesis of InP and InP@ZnS QDs using P4 as a P precursor, which had been simply synthesized from red P powder.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several attempts have been made to use P4 and related compounds as precursors for the synthesis of InP QDs via solvothermal reactions. [56,57] For example, Xie et al reported the solvothermal synthesis of InP nanocrystals using P4 precursor in the presence of the reducing agent KBH4. [56] The size of synthesized nanocrystals was in the range of 11−20 nm, and, further, nanorods with a diameter of 150 nm were produced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation